A comparative study on mental health and adaptability between older and younger adults during the COVID-19 circuit breaker in Singapore - Chou Chuen Yu; Nien Xiang Tou; James Alvin Low (BMC, 2022)
Abstract Background While older age is associated with better emotional well-being, it is unclear whether such age advantages remain during a pandemic. This study examined differences in mental health, adaptive behaviours, social support, perceived stress, digital media usage, and perceived change in circumstances between younger and older adults during the circuit breaker period (partial lockdown) in Singapore. Methods A door-to-door survey was administered to a nationally representative sample of 602 younger (n = 302) and older (n = 300) adults aged 21-89 years from Singapore from 17 October to 27 November 2020. All participants self-reported their depression, anxiety, stress, adaptive behaviours, social support, perceived stress, change in circumstances, and digital media usage during the partial lockdown period. Results Older adults were found to report significantly lower levels of depression, anxiety, and stress as compared to younger adults. Although older adults were less able to perform essential activities during the lockdown, they were more adaptable psycho-socially. Logistic regression analyses revealed that for older age group, adaptability and health status significantly predicted better mental health. Older adults had higher odds of low depression scores [odds ratio (OR) 1.81, 95% confidence intervals (CI) 1.07-3.08], anxiety scores (OR 1.80, 95% CI 1.05-3.08), and stress scores (OR 3.05, 95% CI 1.72-5.41). In addition, adaptability was found to moderate the relationship between age and mental health with detrimental effects of low adaptability stronger for younger adults than older adults. Conclusions During the lockdown period, older adults in Singapore had better mental health, perceived less stress-related concerns and were more adaptable psycho-socially as compared to younger adults. This study's findings extend current evidence that age-related advantages in emotional well-being persisted in the wake of the COVID-19 pandemic.